Was there a ‘the Church’ in the Middle Ages? - Macy, Gary (Studies in church history, 1996)
Scholarly works on the Middle Ages frequently enough mention ‘the Church in the Middle Ages’, or ‘the teaching of the Church in the Middle Ages’ without further specification, as if the reader could immediately identify the institution to which the author is referring. The authors of such works assume both that the reader readily recognizes what the author means by the phrase, but also, and perhaps more troubling, assume that there was an easily identifiable group in the Middle Ages that was ‘the Church’. Yet, when one tries actually to establish some agreement among medieval sources as to what constituted ‘the Church’ or even some agreement as to the criteria by which one could recognize a ‘the Church’, the ‘the Church’ which ought to be so solid seems to disappear into a thousand disparate factions. If, in fact, ‘the Church’ is really better described as a set of common traditions rather than as an institutional monolith, then the question of unity within ‘the Church’ would centre more on the commonality of this tradition than on the structural integrity and uniformity of belief within the institution. In short, how one understands and defines ‘the Church’ will determine the criteria by which one affirms or denies the unity of that Church. A discussion of what ‘the Church of the Middle Ages’ might be seems to be methodologically prior to any determination of the unity or disunity of Christianity in the Middle Ages. This contribution will limit itself to an exploration of some of the problems inherent in assuming that there was a ‘the Church in the Middle Ages’ and, further, that this ‘Church of the Middle Ages’ can be easily identified and defined.